Intervention Strategy using a Role-Playing Technique Approach to Reduce Bullying Behavior among Vocational School Students - Saman, Abdul; Aswar (Department of Guidance and Counseling, FIP, Undiksha, 2024)
Bullying in schools has become a significant problem, negatively impacting students' well-being and psychological development. This phenomenon requires effective intervention strategies to reduce these behaviors among students. This study aims to test the effectiveness of the intervention using the role-playing technique approach in reducing bullying cases in students in Vocational High Schools (SMK). This study uses an experimental quantitative approach with a quasi-experimental design research design, precisely the Pretest-Post-test model, Non-Equivalent Control Group Design. The sample in this study consisted of 8 grade XI students who were identified as experiencing and bullying, which were then divided into two groups: the experimental group and the control group, each consisting of 4 students. The experimental group was given a role-playing technique intervention, while the control group did not receive a similar intervention. Data was collected through interviews, observations, and questionnaires. Data analysis was carried out using descriptive tests and inferential statistics. The results showed that before the intervention, students' bullying behavior was at a high level. However, after the intervention through a five-stage role playing technique, student participation in bullying behavior decreased to a very high and high level. There was a significant difference between the experimental group that received this intervention and the control group that did not. The conclusion of this study shows that intervention through the role-playing technique approach is effective in reducing bullying behavior in grade XI students in vocational schools.